A Morphologically Engineered Robust Bifunctional CuCo2O4 Nanosheet Catalyst for Highly Efficient Overall Water Splitting. Issue 2 (1st December 2019) - Aqueel Ahmed, Abu Talha; Pawar, Sambhaji M.; Inamdar, Akbar I.; Kim, Hyungsang; Im, Hyunsik
Abstract: The development of an earth abundant, low‐cost, and energy‐efficient electrocatalyst with robust adhesion is highly essential for the generation of hydrogen fuel. Herein, the outstanding overall water splitting performance of a CuCo2 O4 catalyst which is fabricated using a hydrothermal process is reported. The performance optimization is done through engineering the surface structure and size of the CuCo2 O4 catalyst, without altering its chemical composition and crystallinity. Different solvents used in the hydrothermal growth tune the morphology of CuCo2 O4 from porous 2‐dimensional nanosheets through cubes and grains to agglomerated spheres. An optimized 2‐dimensional nanosheet CuCo2 O4 catalyst exhibits superior electrochemical performance for both hydrogen evolution reaction and oxygen evolution reaction, achieving the smallest overpotential of 115 and 290 mV versus a reversible hydrogen electrode, respectively, at 10 mA cm −2 with excellent long‐term stability under an alkaline electrolyte medium (1.0 m KOH). This highly stable and electrochemically active bifunctional electrocatalyst can deliver a cell voltage of 1.64 V at 10 mA cm −2 under alkaline condition. Moreover, the correlation between electrochemical catalytic activity with solvent viscosity is manifested in the present study, which reveals that a change in morphologies causes the catalytically active surface area to vary and influences the intrinsic reaction kinetics. Abstract : Template‐free morphologically engineered CuCo2 O4 nanocatalysts are directly fabricated on Ni foam via a single‐step hydrothermal growth technique. A 2‐dimensional porous nanosheet CuCo2 O4 catalyst shows a highly efficient bifunctional electrochemical water splitting activity. This is the consequence of a porous 2‐dimensional nanosheet morphology which endows large electrocatalytically active surface and short diffusion pathways for electrons/ions during electrochemical reaction.